(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Analysis of environment, building and recreational space for elderly center This research is motivated by the existence of the poor facilities of nursing homes for elderly people provided by government. What is needed at present is an alternative residence equipped with recreational facilities to monitor the mental and physical health of the elderly people. This research focuses on environment, building and recreation spot of nursing home. The theories applied in this research include studies dealing with elderly people, the psychology of elderly people, recreation, elderly’s recreation, the design of center for elderly people, and recreational place. The variables examined are environment, building and recreation place. Referring to previous case studies, the environment criteria that will be examined are path of building aspect, on the other hand, communal area, staff and loading areas, building circulation, room unit, balcony, seating area and pantry. Furthermore, of the recreation area, circulation pattern, space organization, activities and shape of the spaces are discussed. Two nursing homes taken as the objects of this tudy are Sasana Tresna Werdha Karya Bhakti Ria Pembangunan and Panti Werdha Wisma Mulia. It is revealed that of the environment aspect Panti Werdha Wisma Mulia is more convenient for elderly’s movements and psychological health as its compound is smaller, which allows the elderly to do activities independently, compared to of the Sasana Tresna Werdha Karya Bhakti Ria Pembangunan nursing home. From the building aspects, on the other hand, Sasana Tresna Werdha Karya Bhakti Ria Pembangunan nursing home has more adequate rooms and better circulation compared to the Panti Werdha Wisma Mulia. Furthermore, of their recreation facilities, the Sasana Tresna Werdha Karya Bhakti Ria Pembangunan has many recreation venues with big capacity and Panti Werdha Wisma has recreation park and function hall. © 2020 Santoni, Francisca Yongsie, Evian Devi